2018
DOI: 10.1016/j.jbiomech.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A subject-specific finite element musculoskeletal framework for mechanics analysis of a total knee replacement

Abstract: Concurrent use of finite element (FE) and musculoskeletal (MS) modeling techniques is capable of considering the interactions between prosthetic mechanics and subject dynamics after a total knee replacement (TKR) surgery is performed. However, it still has not been performed in terms of favorable prediction accuracy and systematic experimental validation. In this study, we presented a methodology to develop a subject-specific FE-MS model of a human right lower extremity including the interactions among the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 54 publications
0
40
0
1
Order By: Relevance
“…Although the muscles considered in this model play the principal role in flexion and extension of the knee (Lieb and Perry, 1968, Fukunaga et al, 1992, Jenkins, 2008, Yeow, 2013, Lube et al, 2016, incorporation of the complete muscles in the lower extremity would further enhance the modelling accuracy. Contact joint models (Chen et al, 2015, Shu et al, 2018 will also be incorporated in future studies to enhance the modelling accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the muscles considered in this model play the principal role in flexion and extension of the knee (Lieb and Perry, 1968, Fukunaga et al, 1992, Jenkins, 2008, Yeow, 2013, Lube et al, 2016, incorporation of the complete muscles in the lower extremity would further enhance the modelling accuracy. Contact joint models (Chen et al, 2015, Shu et al, 2018 will also be incorporated in future studies to enhance the modelling accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…By coupling boundary conditions between a rigid musculoskeletal model and a deformable knee model, predictions of deformation and contact mechanics in the knee were enabled (Halloran et al, 2010, Shu et al, 2018). However, this approach is not suitable for 3D muscles, because boundary conditions of 1D and 3D muscle models cannot be realistically coupled.…”
Section: Introductionmentioning
confidence: 99%
“…The patient-specific geometry of skeletal muscles plays an important role in biomechanical modeling. The computational simulation of human motion using musculoskeletal modeling has been performed in a number of studies to investigate musculo-tendon forces and joint contact forces, which cannot be easily achieved by physical measurements [25], [27], [29]. Recent studies have demonstrated that personalization of model parameters, such as the size of the bones, geometry of the muscles and tendons, and physical properties of the muscle-tendon complex, improves accuracy of the simulation [4], [20], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in order to create the foundations for the development and optimization of the design or the durability of orthopedic implants, it is mandatory to generate appropriate loading conditions that represent inter-patient variability across the population (Honari and Taylor, 2013;Bischoff et al, 2014). Patient-specific finite element analyses are the state-of-the-art technique to infer quantitative information on a specific design or performance of an arthroscopic implant (Shu et al, 2018). Taylor et al (2012) found most studies to be focusing on variations on the morphological and bone properties rather than the consequences of variability because of loading.…”
Section: Introductionmentioning
confidence: 99%